The Dynamics of Policy Communication and Electability: A Case Study of M. Syukur in the 2024 Merangin Regional Elections - Pahrudin HM; Samia Elviria; Supriyanto Supriyanto; Linayati Lestari; Sutri Destemi Elsi; Muhammad Ahalla Tsauro (The Journal of Society and Media, 2026)
This study examines M. Syukur’s political communication strategies and their impact on his electability in the 2024 Merangin Regional Election. In an era of increasing demands for transparency, local issue responsiveness, and digital engagement, effective communication plays a key role in electoral success. Using a qualitative case study approach, this research draws on field observations, in-depth interviews, and content analysis of campaign materials, media coverage, and social media activity. The analysis is guided by political communication theory, agenda-setting, and electability models. The findings reveal that M. Syukur applied a hybrid communication strategy combining a strong digital presence—particularly on Facebook, Instagram, and TikTok—with populist local narratives. His messaging emphasized accessibility, religious-cultural values, and economic empowerment, appealing to rural communities and young voters. Emotional and visual framing helped construct his image as a “candidate of the people,” while grassroots engagement strengthened voter trust.These strategies significantly influenced public perception and voter support across diverse demographics. The study highlights that multi-channel, culturally sensitive communication can enhance candidate visibility, credibility, and electability in local democratic contexts